Reformatorian Youth in the Netherlands: Religiosity and Personality Traits - Bruin, Ria De (Journal of empirical theology, 2024)
In this article, the relationship between Dutch Reformatorian youth’ religious characteristics and their personality traits (measured with the Big Five) is at the centre. It is based on research in which 1568 Reformatorian youth participated, who had enrolled as first-year students in a Reformatorian Vocational Training College. These prospective students have filled in a standard assessment questionnaire, which included the Big Five personality questionnaire; to this, the researchers had added an extra questionnaire regarding their religious characteristics. The conclusions from this study are that among these students a limited number of indications was found for a relationship between religious characteristics and the Big Five personality traits (FFM). By and large, moderate, positive relationships were shown between variables of the Religion List and the personality traits of openness, conscientiousness and agreeableness, whereas there were no relationships between religious variables and emotional stability and small relationships between religious variables and extraversion. Rather than orthodox religious views, it was the salience of faith (being intrinsically religious and using religion as a coping strategy) that showed relationships with the personality traits.